DEBATE IN QS. 2:258 PERSPECTIVE OF RELEVANCE THEORY AND ITS IMPLICATIONS FOR KALĀM LEARNING - Rahmah, Lutfiah; Sopian, Asep; Tantowi, Yusuf Ali (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
This study analyzes communication strategies in the debate dialogue between Prophet Ibrahim and King Namrud in QS. Al-Baqarah verse 258 using Sperber and Wilson’s Theory of Relevance. This study aims to reveal how the cognitive mechanism in the Prophet Ibrahim’s argument can achieve optimal relevance, namely, producing maximum comprehension effects with minimal processing efforts, and examining its implications for the development of the Mahārah al-Kalām learning model. The research uses a qualitative approach with a content analysis design, focusing on the text of Q.S. Al Baqarah, verse 258, as primary data, and studying it through the perspective of Relevance theory. The results of the study demonstrate that the Prophet Ibrahim’s argument succeeded in fulfilling the principle of optimal relevance, thereby giving rise to a model of Qur’anic debate for the study of Mahārah al-Kalām. This model consists of four fundamental stages: first, opening with clear, rational basic premises; second, presenting objections that uphold communication ethics; third, grounding in concrete, irrefutable empirical evidence; and fourth, communicative closure by letting logic speak independently. These findings led to an integrated pedagogical framework that not only pursues linguistic fluency but also trains critical thinking, argumentation, and the ability to present relevant arguments in accordance with the principles of Relevance Theory. The novelty of this research lies in applying pragmatic analysis based on Relevance Theory to uncover the argumentative structure in Qur’anic debate and to transform it into a learning model for Mahārah al-Kalām, designed to cultivate logical, relevant, and ethical speaking skills.